Pengaruh Tingkat Pendidikan, Pemahaman Akuntansi, Sosialisasi, Digitalisasi, dan Penerapan Akuntansi terhadap Penyusunan Laporan Keuangan UMKM di Cikarang - Sri Cahayani; Desfi Intan Fitriani; Supeni Anggraeni Mapuasari (Amal Insani Foundation, 2023)
This research aims to find out the influence of education level, understanding of accounting, socialization, digitalization, and application of accounting on the preparation of MSME financial reports in Cikarang. This research was conducted in Cikarang District, known as one of the cities with the largest industrial area in Southeast Asia, which is also the place where millions of migrants live. The data used in this study are primary data collected through questionnaires and the measurement technique used is the Likert scale technique. The population in this study are all MSME actors in Cikarang District, totaling 972 actors registered at the Badan Pusat Statistik (BPS) of Bekasi Regency. The sampling size was determined using the Slovin formula which was reflective of the population in this research, from the calculations of the Slovin formula 100 MSMEs in Cikarang that were used in this research. Data analysis techniques consisting of data quality tests, statistical descriptive tests, validity and reliability tests, multicollinearity, and t-tests are used to evaluate the data's quality by using SPSS version 23 for Windows. The study results show that the variables of education level, understanding of accounting, digitalization, and application of accounting have a positive effect on the preparation of MSME financial statements. While the socialization variable has no positive effect on the preparation of MSME financial reports. It can be concluded that several MSMEs in Cikarang have implemented simple bookkeeping such as recording sales, purchases, inventories, cash inflows and outflows, and other costs. However, process recording up to financial reporting has not been implemented optimally. This study result suggests that the government should focus on improving several variables that support MSMEs' ability to prepare financial statements.